Ferritin in Adult-Onset Still’s Disease: Just a Useful Innocent Bystander? - Bella Mehta; Petros Efthimiou (International Journal of Inflammation)
Background. Adult-Onset Still’s Disease (AOSD) is an immune-mediated systemic disease with quotidian-spiking fever, rash, and inflammatory arthritis. Hyperferritinemia is a prominent feature, often used for screening. Methods. The key terms “ferritin” and “hyperferritinemia” were used to search PubMed and Medline and were cross-referenced with “Still’s Disease.” Results. Hyperferritinemia, although nonspecific, is particularly prevalent in AOSD. While most clinicians associate ferritin with iron metabolism, this is mostly true for the H isoform and not for the L isoform that tends to increase dramatically in hyperferritenemia. In these situations, hyperferritinemia is not associated with iron metabolism and may even mask an underlying iron deficiency. We review, in systematic fashion, the current basic science and clinical literature regarding the regulation of ferritin and its use in the diagnosis and management of AOSD. Conclusion. Serum hyperferritinemia in AOSD has been described for 2 decades, although its mechanism has not yet been completely elucidated. Regulation by proinflammatory cytokines such as interleukin (IL)-1b, IL-6, IL-18, MCSF, and INF-α provides a link to the disease pathogenesis and may explain rapid resolution of hyperferritinemia after targeted treatment and inhibition of key cytokines.